Irrigation system and productive strategies in the Andean peasant economies - Claverías H., Ricardo (1986)
In this paper we are interested in dealing with the problem of water and its use, as a central component of the technological package produced and used within the economic, social and cultural rationality of Andean peasant economies. The interest in dealing with this topic comes from the following questions that, apparently, are part of the common sense of many technicians and professionals related to agricultural activities: for example, some affirm that the agrarian problem in Peru is not the land but Water; Others affirm that the transfer of modern technologies in general and in particular in modern irrigation are the solution for the productive development of Peruvian agriculture.